Determinan faktor yang berhubungan dengan cakupan imunisasi dasar pada balita di Pidie, Aceh: Studi potong lintang - Masyudi Masyudi; Namira Yusuf; Yuliani Safmila; Jailani Jailani; Muhammad Ridhwan (Jurnal SAGO Gizi dan Kesehatan, 2023)
Background: Immunization coverage in Pidie Aceh Still has not met the targets. Based on data from the Pidie Health District Office, it is known that the coverage of complete basic immunization for toddlers has only reached 84,84%. The Regional Government and related agencies are still working on various programs to achieve this. Several factors affect the coverage of basic immunization in an area, such as the low role of cadres and the lack of family support for immunization. An assessment must be conducted to determine good policies for future health programs.Objective: The research aims to determine the factors that cover the basic immunization program for toddlers in Kembang Tanjong, Pidie-Aceh.  Method: This research is descriptive-analytic with a cross-sectional study design. Sampling using probability sampling was carried out on 100 respondents. This research was carried out from 03 to 11 December 2020 in the Kembang Tanjong, Pidie, Aceh. Data were collected through interviews using a questionnaire. Analysis used the Chi-Square test at 95% CI.Research result: This study has found a relationship between the role of cadres (p= 0,015), family support (p= 0,025), and the role of health workers (p= 0,040), as well as the role of religious leaders (p= 0,033) with the coverage of the basic immunization program for toddlers.Conclusion: Family support, the role of officers, and the role of religious leaders greatly influence whether immunization results are achieved in Pidie Aceh. Therefore, these three factors need to be considered.